REAKSI PASAR TERHADAP PENGUMUMAN DIVIDEN TUNAI DI INDONESIA TAHUN 2012 - ., Anita; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 8 No 1 (2014), 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Information content of cash dividend announcement at the Indonesia Stock Exchange in 2012 , and the difference between market reactions to the results of listed companies announced cash dividend increases and decreases observed using purposive sampling method with 181 issuers as 125 companies that announced dividend increases , 39 companies announced dividend decrease and 17 companies announcing dividend remains . The results of the event study test one sample t -test showed that dividend announcement have information content both for the overall sample and the sample of issuers listed companies announced cash dividend increases and decreases, and two different test average shows that different markets react significantly to announcement of cash dividend increases and cash dividend decrease . AAR for increase in the cash dividend is higher than the AAR decrease in cash dividends .
Keywords: Market Reaction; abnormal return; cash dividend